Assessing the Impact of COVID-19 Pandemic on the Regions’ Socio-Economic Development: The Case of Ukraine - Hryhoruk, Pavlo; Khrushch, Nila; Grygoruk, Svitlana; Gorbatiuk, Kateryna; Prystupa, Liudmyla (European Journal of Sustainable Development, 2021)
Solving the problems of regional development belongs to the category of strategic and most important of each country. The COVID-19 pandemic has become the biggest challenge for the world economic system, causing a significant impact on the reduction of key macroeconomic indicators, changes in business conditions, which has raised the issue of assessing the social and economic development of regions. The paper considers the application of composite index assessment technology for the consequences of COVID-19 on the development indicators of Ukraine's regions. The comparison was conducted according to the data of the first two quarters of 2019 and 2020. For the study, eight indicators were selected, which by content feature were divided into a subset of economic indicators and a subset of social indicators. A partial composite development index was designed for each subset. The principal components method was used to calculate the weights of the components. The results of the analysis showed that the COVID-19 pandemic had a greater impact on economic development: for each region, there is a decrease in the value of the indicator. While for a partial composite index of social development such a decrease is less noticeable. The reflection of the regions in the space of these composite indices showed that their structure remained virtually unchanged. The analysis of the common composite index of regional development, designed by the convolution of partial composite indices indicators, also showed a decrease in its values in 2020. The paper analyses the measures taken by the Government of Ukraine to neutralize the effects of the pandemic.